Legal Reconstruction of Electronic Health Data Protection in Indonesia's Digital Health Ecosystem - Dhian Indah Astanti; Anggraeni Endah Kusumaningrum (Sabtida, 2026)
The rapid expansion of Indonesia’s digital health ecosystem has heightened the urgency for strong legal protection of electronic health data. Existing frameworks, including the 1945 Constitution, Law No. 27/2022 on Personal Data Protection, Law No. 17/2023 on Health, Government Regulation No. 71/2019, and Minister of Health Regulation No. 24/2022, remain weakened by regulatory inconsistency, fragmented governance, limited institutional coordination, and insufficient regulation of emerging technologies. This study employs normative juridical research with statutory, conceptual, and comparative approaches, supported by qualitative prescriptive analysis. Comparative references to the EU’s GDPR and the US HIPAA highlight internationally recognized standards. Findings indicate that incremental amendments are inadequate, and comprehensive legal reconstruction is required. To address this, the Five-Pillar Legal Protection Model is proposed: Legal Substance Reform, Institutional Governance, Cybersecurity Integration, Patients’ Rights Protection, and Oversight and Law Enforcement. This model advances legal protection scholarship by transforming conventional frameworks into an integrated governance system that enhances legal certainty, institutional accountability, cybersecurity resilience, and patient rights within Indonesia’s digital health ecosystem.